Monte Carlo Simulation for Designing Collimator of the Neutron Radiography Facility in Malaysia - Jamro R.; Kardjilov N.; Hairierabir M.; Zain M.R.M.; Mohamed A.A.; Ali N.M.; Idris F.; Ahmad M.H.A.R.M.; Yazid K.; Yazid H.; Azman A.; Mamat M.R. (Elsevier B.V., 2023)
Intelligent systems; Neutron radiography; Neutrons; Nuclear reactors; Beam characteristics; collimator; Collimator Geometry; Gamma fluxes; Object planes; Sample position; Thermal neutrons; Thermal-neutron flux; Monte Carlo methods